DEVELOPMENT OF AUDIOVISUAL-BASED LEARNING MEDIA ON THE SUBJECT OF IMMUNE SYSTEM AT SMA NEGERI 12 MEDAN - Nadia Suranta Sembiring; Erlintan Sinaga; Tonggo Sinaga; Wasis Wuyung Wisnu Brata (Jurnal Pelita Pendidikan, 2022)
This research aims to develop audiovisual-based learning media on the topic of the immune system in class XI of SMA Negeri 12 Medan during the academic year 2021/2022. The method used in this study is research and development. The research subjects consist of Subject Matter Experts, Learning Media Experts, Biology Subject Teachers, and students of class XI MIA at SMA Negeri 12 Medan. Data collection was conducted through instruments such as expert validation assessment sheets, teacher assessments, and student responses. The development of learning media was carried out using the 4D instructional development model (Define, Design, Development, and Disseminate). Each stage of this model underwent revisions to produce high-quality audiovisual learning media products. The results of the study showed that the assessment by subject matter experts obtained a percentage of 100% (Highly Suitable), the assessment by learning media experts obtained a percentage of 82.81% (Suitable), and the assessment by the biology subject teacher obtained a percentage of 100% (Very Good). The students' feedback and responses to the learning media also obtained a percentage of 81.66% (Very Good). The results of the comprehension test on the learning media for the students, based on the pretest scores, showed an average of 49.75 (Low), while the posttest results showed an average of 76.96 (High). Thus, it can be concluded that the audiovisual learning media on the topic of the immune system meet the criteria of being "Highly Suitable" and fulfill the requirements in the biology learning process.